1961
DOI: 10.1029/jz066i004p01081
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of equatorial spreadF

Abstract: Ionospheric propagation via scattering from the F region was sought at 50 Mc/s over a transequatorial path (with midpoint near Huancayo, Peru) employing a 2580‐km transmitter‐receiver separation. Propagation via F scatter was present over this path about 10 per cent of the time, though only at night. A condition closely related to the occurrence of F scatter was the presence of equatorial spread‐F configurations on the Huancayo ionograms. The height of the propagation medium supporting this F scatter was usual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0

Year Published

1961
1961
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…The equatorial belt between magnetic latitudes 20 • N and 20 • S is a well defined region where spread-F is a normal occurrence and has been described and studied in depth since the 1950s (Wright, 1959;Cohen and Bowles, 1961;Balsley et al, 1972;Aarons, 1978;Fejer et al, 1979;Argo et al, 1986;Mendillo et al, 1992;Whalen, 2000;McNamara et al, 2008). This is because, while the post-sunset rise (PSSR) of the equatorial F layer is well correlated climatologically with the equatorial spread-F (ESF) (Fejer et al, 1999;Hysell and Burcham, 2002), the day-to-day variability of ESF remains a long-standing enigma.…”
Section: Introductionmentioning
confidence: 99%
“…The equatorial belt between magnetic latitudes 20 • N and 20 • S is a well defined region where spread-F is a normal occurrence and has been described and studied in depth since the 1950s (Wright, 1959;Cohen and Bowles, 1961;Balsley et al, 1972;Aarons, 1978;Fejer et al, 1979;Argo et al, 1986;Mendillo et al, 1992;Whalen, 2000;McNamara et al, 2008). This is because, while the post-sunset rise (PSSR) of the equatorial F layer is well correlated climatologically with the equatorial spread-F (ESF) (Fejer et al, 1999;Hysell and Burcham, 2002), the day-to-day variability of ESF remains a long-standing enigma.…”
Section: Introductionmentioning
confidence: 99%
“…The signatures employed are the diffuse echoes that were first described in equatorial ionograms by Booker and Wells [1938]. These echoes were identified as range spread F (RSF) resulting from field-aligned irregularities by Cohen and Bowles [1961], who named them equatorial spread F. Weber et al [1978] found these echoes to be associated with bubbles as identified by their coincidence with depletions of airglow at 6300 •.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the enhanced electron density is to create errors in the Global Positioning System and radar location and also to interfere with HF propagation. Both bubbles and BSSF produce a signature in vertical ionograms that was named equatorial spread F by Cohen and Bowles [1961], a term that unfortunately has come to be equated with bubbles. This work will describe this signature as range spread F (RSF) and will distinguish the bubble from BSSF by determining that the bubble extends to much higher latitude hence altitude and is confined to a narrow longitudinal extent as it drifts eastward.…”
Section: Introductionmentioning
confidence: 99%